Etiological factors involved in recurrent abortion - Gonzales, Wilfredo (2015)
Retrospective, descriptive study to determine tb etiological factors in recurrent abortion in patients attended at Guillermo Almenara Irigoyen National Hospital Obstetrical Service between 1993 and 1995 -Findings in 42 patients with 2 or more consecutive abortions showed autoimmune disorder in 11,9 uterine anatomical defect in 9,5%, and hormona infectious and genetic abnormalities in 7,1%, 4,8 and 2,4%, respectively. No cause was found in 64,3 We consider we did not find the etiological factor i the majority of cases because of insufficient technology.